Commercialization of Pesantren: Challenges and Opportunities in Preserving the Authenticity of Islamic Education in Indonesia - Jamroji, Bagus (Academia Publication, 2024)
This study explored the impact of commercialisation on pesantren education in Java, particularly in maintaining the authenticity of its traditional values. Pesantren face the challenge of modernisation that encourages the adoption of the national curriculum and cooperation with the private sector, which may reduce the focus on religious education. This study used the literature study method to analyse the challenges and opportunities faced by pesantren. The findings revealed that while commercialization could erode traditional values and widen educational inequality, it also presents opportunities for pesantren to innovate in curriculum development, enhance facilities, and integrate modern teaching methods. In conclusion, with the right strategies, pesantren can maintain their identity while adapting to market demands, thus remaining relevant in the changing social and economic context.